2011
DOI: 10.1103/physrevd.83.094505
|View full text |Cite
|
Sign up to set email alerts
|

Resonance parameters of theρmeson from lattice QCD

Abstract: We perform a non-perturbative lattice calculation of the P-wave pion-pion scattering phase in the ρ-meson decay channel using two flavors of maximally twisted mass fermions at pion masses ranging from 480 MeV to 290 MeV. Making use of finite-size methods, we evaluate the pion-pion scattering phase in the center-of-mass frame and two moving frames. Applying an effective range formula, we find a good description of our results for the scattering phase as a function of the energy covering the resonance region. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
288
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(304 citation statements)
references
References 38 publications
(35 reference statements)
13
288
2
1
Order By: Relevance
“…In particular, the Lüscher method and its extensions for relating finite-volume spectra to scattering amplitudes are now well established for elastic [5][6][7][8][9][10][11][12][13][14] and coupled-channel [15][16][17][18][19] hadron-hadron scattering. These methods have been demonstrated in a number of applications, notably for the ρ-resonance seen in P -wave ππ scattering [20][21][22][23][24][25][26][27][28][29], and for the σ resonance seen in S-wave ππ scattering [30]. It has also recently been shown that, with sufficiently extensive and precise spectra, information on coupled-channel hadron-hadron scattering amplitudes can be obtained [26,[31][32][33] -this is crucial for understanding highly excited states that are typically kinematically permitted to decay into several channels.…”
Section: Jhep10(2016)011mentioning
confidence: 99%
“…In particular, the Lüscher method and its extensions for relating finite-volume spectra to scattering amplitudes are now well established for elastic [5][6][7][8][9][10][11][12][13][14] and coupled-channel [15][16][17][18][19] hadron-hadron scattering. These methods have been demonstrated in a number of applications, notably for the ρ-resonance seen in P -wave ππ scattering [20][21][22][23][24][25][26][27][28][29], and for the σ resonance seen in S-wave ππ scattering [30]. It has also recently been shown that, with sufficiently extensive and precise spectra, information on coupled-channel hadron-hadron scattering amplitudes can be obtained [26,[31][32][33] -this is crucial for understanding highly excited states that are typically kinematically permitted to decay into several channels.…”
Section: Jhep10(2016)011mentioning
confidence: 99%
“…The b 1 channel also couples to η 2 ρ, its contribution might be relevant only above threshold for energies above O(1.5) GeV and we omit this interpolator. 2 To summarize, we assume that the elastic scattering ρπ and ωπ dominates both channels in the energy region of interest and rely on the same assumption when extracting Γ a 1 →ρπ and Γ b 1 →ωπ from the experimental data. We note that the inelastic scattering with coupled channels has not been treated in lattice simulations yet, while the analytic frameworks for this challenging problem were developed, for example, in [34][35][36][37].…”
Section: Jhep04(2014)162mentioning
confidence: 99%
“…The ρ mass in table 2 was extracted as m ρ = E ρ (p = 0) in [3] and is indeed found close to m res ρ in all simulations [1][2][3][4][5][6]. The ω energy is calculated using quark-antiquark interpolators O s=n 1−5 given by eq.…”
Section: Masses Of π ρ ωmentioning
confidence: 99%
See 1 more Smart Citation
“…This method converts binding energies of a hadron-hadron system in the finite box into phase shifts of hadron-hadron interaction from levels above threshold, or binding energies from levels below threshold [4][5][6]. From the phase shifts one can get resonance properties, and there are several works that have recently applied these techniques to study the ρ resonance [7][8][9][10][11][12][13][14][15]. There exist other resonances far more difficult to get with this approach like the a 1 (1260), which was also attempted in [14] (see also its determination using finite volume calculations with effective field theory in [16]).…”
Section: Introductionmentioning
confidence: 99%